Comparison of trunk and arm movement sequences of javelin throwers with short and long official distances - Liu, H.; Yu, B. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to determine the effects of the sequences of initiations of trunk and upper extremity angular motions on the performance of javelin throwing. The sequences the initiations trunk and arm angular motions and maximum angular velocities were determined for 32 male and 30 female elite javelin throwers, and compared between groups with short and long official distances. Throwers with short and long official distances employed same sequences of trunk and arm angular motions. Male and female throwers employed different sequences of the trunk and arm angular motions. The sequence of the initiations of trunk and arm angular motions was different from that of the maximum trunk and arm angular velocities.